The Research in Constitucional Law as a factor of interdisciplinary opening in Law researching in Brazil: - (Reflection and Critique Law Magazine, 2024)
The discussion about methodological approaches in Law researches is frequently leaded to discussions about the very scientific character of Law itself, or even about the instrumental nature of Law in Brazil. Among the problems pointed out in legal research, the subject of this paper is cut around two aspects: the confusion between professional legal practice and academic research, and the barriers found between Law and other disciplines in the social and humans sciences. This paper, based on readings that point to problems in research in Law schools in Brazil, surrounds the hypothesis that Constitutional Law is an essentially interdisciplinary field of study, so that research in Constitutional Law may come to be considered an opening field for interdisciplinary approaches in Law research as a whole. The hypothesis raised is justified insofar as the interdisciplinary approach essential to Constitutional Law can serve as a mean of overturning or at least softening the borders between Law and other disciplines of social and human sciences, as well as an updated study in Constitutional Law can also be able to put in critical perspective the influence of legal formalism in the way of doing research in Law in Brazil.